PENGEMBANGAN MEDIA PAPAN SCRABBLE SISTEM PEREDARAN DARAH TERHADAP KEAKTIFAN SISWA SEKOLAH DASAR - Triyanti, Triyanti; Hakim, Lukman; Lefudin, Lefudin (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to develop a science learning media in the form of a Scrabble board using recycled materials to enhance student engagement in the topic of the circulatory system for fifth-grade elementary students. The research model employed is Research and Development (R&D), utilizing the 4D development model which includes the stages of Define, Design, Development, and Dissemination. The overall result of the validity test for the Scrabble board learning media on the human circulatory system topic yielded a score of 93.19%, indicating that the product meets the criteria of being highly feasible and is therefore considered very valid. The overall practicality score was 94.31%, also indicating that the product meets the criteria of being highly feasible and is thus considered very practical. Based on the evaluation results from the pretest and posttest, the students’ pretest scores before the learning process showed a percentage of 62.29%, categorized as less satisfactory. Meanwhile, the posttest results showed that students had reached the target with a percentage of 90%, categorized as highly effective. In conclusion, the developed Scrabble board media is valid for use in the learning process and can improve elementary students' engagement.